DEVELOPMENT OF LEARNING MEDIA USING ADOBE AFTER EFFECT IN DYNAMIC ELECTRICITY SUBJECT MATTER - Ony Aldinan Satra; Sukainil Ahzan; M. Fuaddunazmi (Universitas Pendidikan Mandalika, 2016)
This research is the development of instructional videos. The purpose of this study was to develop ICT based learning media that can enhance students' understanding on the dynamic electrical material. This study uses 4D model of development which define, design, develop and disseminate. This study only uses three phases to the development stage video designed using Software adobe after effect. Further testing in two stages, the process of validation and surveys. The validation process performed by the second validator of the quality and appropriateness of instructional media content with an average score of 3.25 thus classified as